IN VITRO ACTIVITY OF MEDICINAL PLANTS AGAINST SOME BACTERIAL AND FUNGAL ISOLATES - RP, Mishra; Javed, Iqbal (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Based upon the local availability and medicinal values, leaves of four plants i.e. Azadirachta indica L., Jatropha curcas L., Ocimum gratissimum and Cuscuta reflexa Roxb were collected. The plants were indentified based on their description given in the literature. Leaves were powdered after drying at 370C for 3 to 10 days. Exposure to sunlight was avoided to prevent the loss of active compounds. The completely shade dried material was coarsely powdered and put in soxhlet for successive extraction with different solvents like, petroleum ether, ethyl acetate and methanol. Four fungal species were isolated and identified from the soil sample collected from different places of Jabalpur (M.P.). Aspergillus niger was most frequent 60% followed by Aspergillus flavus (20%), Penicillium notatum (10%), Fusarium oxysporium (10%). Results obtained during assay with plant extracts from Azadirachta indica, Ocimum gratissimum, Jatropha curcas and Cuacuta reflexa leaves showed their inhibitory effect against some fungal and bacterial isolates. Key words;Isolates,Medicinal